Pump‐controlled retrograde trial off for weaning from venoarterial extracorporeal membrane oxygenation in an adult patient with pulmonary embolism. Issue 1 (11th December 2022) - Matsumura, Kazuki; Matsuyoshi, Takeo; Horikoshi, Yuichi; Sasaki, Junichi; Shimizu, Keiki
Abstract : Background: Although pump‐controlled retrograde trial off (PCRTO) is a practical method for weaning from venoarterial extracorporeal membrane oxygenation (VA‐ECMO), its advantages and safety for patients with pulmonary embolism are not yet reported. Case Presentation: A 62‐year‐old man with coronavirus disease 2019 experienced sudden cardiac arrest, and VA‐ECMO was introduced. After confirming a massive acute pulmonary embolism, unfractionated heparin treatment was initiated. On day 6, the patient was confirmed stable with a flow rate of 1.0 L/min. However, decannulation led to cardiac arrest and reintroduction of VA‐ECMO. After further treatment, a residual thrombus was observed, and pulmonary arterial pressure remained high. On day 23, ECMO was decannulated successfully after a weaning test with PCRTO, which simulated ECMO withdrawal by generating a partial arteriovenous shunt. Conclusion: PCRTO is a feasible weaning strategy and can be considered for patients with uncertain cardiorespiratory recovery. Abstract : Although pump‐controlled retrograde trial off (PCRTO) is a practical method for weaning from venoarterial extracorporeal membrane oxygenation (VA‐ECMO), its advantages and safety for patients with pulmonary embolism are vague. We report a patient with pulmonary embolism who was successfully decannulated after VA‐ECMO with PCRTO. As PCRTO can effortlessly and precisely simulate ECMO withdrawal, it is an effective weaning strategy for patients with marginal cardiac recovery.